Microsurgical Resection of the Epidermoid Tumor in the Cerebellopontine Angle - Pojskić, Mirza; Arnautović, Kenan I. (Journal of Neurological Surgery Part B: Skull Base, 2019)
In this video, we demonstrate epidermoid tumor microsurgical resection of the cerebellopontine angle (CPA) performed by the senior author (K.I.A.). Epidermoid tumors arise from ectoderm trapped within/displaced into the central nervous system. They show predilection for CPA Angle (up to 40%), 4th ventricle, suprasellar region, and spinal cord.1 They are the 3rd most common CPA tumor, comprising approximately 7% of CPA pathology. CPA lesions can produce 5th and 7–12th cranial nerve neuropathies.234 Recurrent episodes of aseptic meningitis caused by cyst content rupture may occur. Symptoms include fever, meningeal irritation, and hydrocephalus. A 26-year-old female presented with headaches. Head magnetic resonance imaging (MRI) revealed right CPA tumor with brain stem compression (Fig. 1, A–C). There was evidence of restricted diffusion in diffusion-weighted imaging, typical of epidermoid tumor. Surgery was performed in prone position with head turned 25 degrees to the ipsilateral side using retrosigmoid craniotomy.5 Tumor was ventral to the 7th and 8th cranial nerve complexes, between the 5th nerve as well as toward the brainstem. The surgical plan was gross total resection with tumor capsule resection to prevent recurrence.6 (Small residuals can be left behind when capsule is adherent to critical structures.) Tumor was adherent to brain stem perforators which were preserved using meticulous dissection. Cranial nerves and vascular structures were also left intact. We irrigated with antibiotic saline and used perioperative treatment to prevent aseptic meningitis. The pathohistological diagnosis revealed epidermoid tumor cyst. Postoperative MRI revealed complete resection (Fig. 1, D–F). The patient recovered fully and was neurologically intact.The link to the video can be found at: https://youtu.be/LyWl-KZUSGY.
Keywords: cerebellopontine angle; epidermoid tumor; epidermoid tumor cyst; microsurgery